A new large and colorful skink of the genus Amphiglossus from Madagascar revealed by morphology and multilocus molecular study - Miralles, Aurélien; Raselimanana, Achille P.; Rakotomalala, Domoina; Vences, Miguel; Vieites, David R. (Zootaxa, 2011)
We describe a new species of Amphiglossus skink from the western edge of the Central Highlands of Madagascar in the Reserve of Makira, and also found in the Réserve Spéciale of Ambohijanahary and in the Réserve Spéciale of Marotandrano. Amphiglossus meva n. sp. is characterized and differentiated from other species of the genus by a combination of morphological, chromatic and molecular characters: 1) a relatively large size (SVL of adults from 126 to 150 mm); 2) a characteristic pattern of coloration, Amphiglossus meva being the only skink in Madagascar together with Amphiglossus crenni with dark grey dorsum contrasting with orange flanks and ventrum; 3) the absence of a postnasal scale; 4) the presubocular frequently absent, 5) the presence of single elongated tertiary temporal bordering lower secondary temporal and 6) pentadactyl limbs. In addition to the morphological approach, a multi-locus genetic analysis based on eight mitochondrial and nuclear genes clearly supports the distinctiveness of A. meva. This new species was found in areas of rainforest, sometimes containing transitional deciduous forest elements. It was typically observed under large rotten logs associated with dense layers of decomposed wood retaining certain humidity and providing habitat for invertebrate larvae and termites.